objectif_projects 2002-2003. - Pirotte, Philippe; Van den Abbeele, Win; Van Rossem, Patrick; Vermeiren, Gerrit (Antwerp : objectif_exhibitions, 2004)
Arocha, Carla ; Legrand, Jozef ; McCorkle, Corey ; Cabrita Reis, Pedro
boek